Reform of Islamic Theology in India: Sheikh Waliullah Ad-Dahlawi and Syed Ahmad Khan - Mujibuddin , M; Abrahem Masuwd, Mowafg; Irfan Achfandhy, Mochammad (STAIN Sultan Abdurrahman Kepulauan Riau, 2024)
The decline of the Muslim community in India during the 18th and 19th centuries was attributed to both internal and external factors. Internally, it was driven by the collapse of the Mughal dynasty, particularly after the death of Emperor Aurangzeb. This internal decline was also exacerbated by stagnation within the Indian Muslim community. Externally, the influence of modern Western knowledge introduced by the British played a significant role. These two factors prompted theological movements initiated by Syaikh Waliyullah ad-Dahlawi and Seyyed Ahmad Khan, both of whom aspired to uplift the Indian Muslim community from its backwardness. The efforts of these two scholars were focused on reconstructing the theological framework that had long been established among Indian Muslims. Syaikh Waliyullah ad-Dahlawi aimed to free the Muslim community from religious orthodoxy. Meanwhile, Seyyed Ahmad Khan, in addition to advancing ad-Dahlawi’s efforts, introduced fresh ideas regarding Islamic education. Seyyed Ahmad Khan successfully integrated Islam as a religion with modern education, culminating in the establishment of the Mohammedan Anglo-Oriental College (M.O.A.C.), later known as Aligarh Muslim University. At the time, this institution became one of the largest centers of Islamic learning in Asia. Kemunduran umat Muslim di India pada abad 18-19 disebabkan oleh dua faktor, yaitu faktor eksternal dan internal. Faktor internal disebabkan karena adanya kehancuran dinasti Mughal, terutama setelah kematian raja Aurangzeb. Di sisi lain, faktor internal ini juga disebabkan adanya kejumudan dalam umat muslim India. Sedangkan faktor eksternal disebabkan adanya ilmu pengetahuan modern Barat yang dibawa oleh Inggris. Kedua faktor tersebut yang mempengaruhi adanya gerakan teologi yang diprakarsai oleh Syaikh Waliyullah Ad-Dahlawi dan Seyyed Ahmad Khan. Kedua ulama tersebut sama-sama menginginkan agar uma muslim India bisa bangkit dari keterbelakangannya. Upaya yang dilakukan oleh kedua orang tersebut adalah dengan merekonstruksi teologi yang selama ini sudah mapan di muslim India. Syaikh Waliyullah ad-Dahlawi menginginkan agar umat Islam terbebas dari ortodoksi agama. Sedangkan Seyyed Ahmad Khan, di samping menyempurnakan usaha ad-Dahlawi, Seyyed Ahmad Khan juga memberikan pemikiran segar tentang pendidikan Islam. Seyyed Ahmad Khan berhasil memadukan antara Islam sebagai agama dan pendidikan modern. Hasilnya berupa berdirinya sekolah Mohammaden Anglo Oriental Collage (M.O.A.C.) atau dikenal dengan Universitas Islam Aligarh yang pada saat itu menjadi salah satu universitas Islam besar di Asia.